2011
DOI: 10.3109/03630269.2011.576153
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Compliance And Toxicity Factors Are Affecting The Rate Of Normalization Of Body Iron Stores In Thalassemia Patients Using The Deferiprone And Deferoxamine Combination Therapy

Abstract: The international committee on chelation (ICOC) of deferiprone (L1) and deferoxamine (DFO) combination therapy was the first protocol reported to have achieved normal range body iron store levels (NRBISL) in β-thalassemia major (β-TM) patients. A follow-up study in eight β-TM patients has been designed to investigate the factors affecting the rate of iron removal leading to NRBISL. The patients had variable serum ferritin [mean ± SE (standard error) =1692 ± 366, range 539-3845 μg/L)] and magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 25 publications
4
32
0
Order By: Relevance
“…Our present findings confirm previous observations [11,12,13] and validate our hypothesis, as satisfactory ferritin levels were achieved in our study population, which were markedly lower than those reported in earlier studies [2,3]. The results of univariate and discriminant analyses reinforce these considerations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our present findings confirm previous observations [11,12,13] and validate our hypothesis, as satisfactory ferritin levels were achieved in our study population, which were markedly lower than those reported in earlier studies [2,3]. The results of univariate and discriminant analyses reinforce these considerations.…”
Section: Discussionsupporting
confidence: 82%
“…This view was based on accumulated evidence, indicating that current chelation therapy is effective [11] and is associated with high patient compliance rates [12,13]. A previous study from our Institution demonstrated that combined chelation therapy with deferoxamine and deferiprone results in a satisfactory reduction of serum ferritin without significant toxicity [9].…”
Section: Discussionmentioning
confidence: 99%
“…Such protection effect was presented in our in vitro study by deferiprone, the effective iron chelator commonly used in current clinical practice [51]. However, in our assessment, none of the calcium channel blockers showed significant protection effect on iron overload induced apoptosis, though LTCC blockers, in particular amlodipine, presented slight protection at 600 µM of ferric or ferrous iron challenge.…”
Section: Discussionsupporting
confidence: 58%
“…Variations in compensatory mechanisms and alternative metabolic pathways which are in operation in affected cells and tissues may contribute to minimising the severity of FA [85] . Similar variations are observed in other inherited and metabolic diseases including TM and hereditary haemochromatosis [13,62,[85][86][87] . Deficit of frataxin is mostly related to many abnormalities associated with mitochondrial structure and function.…”
Section: Ataxiasupporting
confidence: 50%